Study of High Performance Liquid Chromatography and Turbidimetric Inhibition Immunoassay for HbA1c Analysis in Diabetic Patients with Variant Hemoglobin - Sultana, Gazi Sharmin; Khan, Nadia Zebin; Khuda, Zannat e; Sultana, Tanvira Afroze; Dipta, Tashmim Farhana; Muttalib, MA; Choudhury, Subhagata (BIRDEM Medical Journal, 2018)
Background: HbA1c is considered as “gold standard” to evaluate glycemic control in patients with diabetes. Hemoglobin variants are mutant forms of hemoglobin that can occur by genetic changes in specific amino acid that can affect the accuracy of HbA1c measurements. High performance liquid chromatography (HPLC) is the standard method for HbA1c but inaccurate HbA1c values can occur when hemoglobin variants are present in diabetic patient. The aim of our study is to see Turbidimetric Inhibition Immunoassay (TINIA) method can report HbA1c values in diabetic patients with variant hemoglobin when the values are inaccurate on HPLC. Methods: 7590 diabetic patients were analyzed for HbA1c by HPLC method from BIRDEM General Hospital during December 2013 to January 2014. HbA1c levels were again measured by TINIA method in 50 cases out of 7590 who showed either undetectable / below normal HbA1c levels. Hb electrophoresis confirmed the variant hemoglobin in few cases Results: 50 cases out of 7590 (0.65%) had either undetectable / below normal HbA1c levels by HPLC method. Males-26 and females-24; and the ratio was 0.92:1. In 27 cases, HbA1c values were undetectable by HPLC method but in the reportable range by TINIA method. In the other 23 cases, HbA1c levels were below the reportable range (<4%) by HPLC method but were in the normal or higher range by TINIA method. On Bland Altman plot, TINIA method did not agree with HPLC method in variant cases. Conclusion: In South East Asia where Hb variant is high, Low or undetectable HbA1c level by HPLC may be a convenient clue for screening of hemoglobinopathies especially among diabetic population in Bangladesh. All laboratories should have alternative method of HbA1c testing like TINIA along with HPLC for correct determination of glycemic control in variant cases Birdem Med J 2018; 8(2): 114-117